317. Administered activities and effective dose optimization in 18F-FDG PET/CT and 123I-MIBG SPECT/CT examinations in patients during oncology follow-up. (December 2018) - Fabbri, C.; Giorgetti, G.; Del Dottore, F.; Dall'Ara, D.; Busca, F.; Casi, M.; Mattone, V.; Marchi, G.; Bartolini, N.; Sanniti, S.
Abstract : Purpose: The evaluation of the mean effective dose (ED) in repeated nuclear medicine scans in order to optimize the administered activity in 18 F-FDG PET/CT[1] and 123 I-MIBG SPECT/CT[2] acquisitions in adult and paediatric patients (pts) respectively, during oncology follow-up. Materials and methods: SPECT-CT acquisitions were performed by Symbia T2, Siemens. The CT acquisition was performed using a tube current modulation system. Parameters used were: tube current of 30–60 mAs, slice thickness of 5 mm, pitch 2 and tube voltage of 110 kV. Whole body scans were assessed by Discovery 710 Elite (GE) PET/CT equipment. The CT acquisitions parameters were as follows: 120 kV tube voltage, 18–60 mAs tube current, 3.75 mm slice width, 0.6 s rotation time. The activities administered to the pts during 4494 18 F-FDG PET/CT and 54 123 I-MIBG SPECT/CT performed at the Nuclear Medicine Department of the Bufalini Hospital (Cesena) were analyzed by acquiring the data relative to the exams done in 2015–2016 directly from the digitalized registration system (ASTRIM). The data processing was realized by using a home-made and web-based software implemented in asp language. The values were divided based on patient's gender, age and weight. Moreover, it was verified how many times and how often the same pt repeated the exam. Eventually, the total mean EDTOT in male and female was calculated with administered activity by using ICRP128 coefficients (mSv/MBq) and from the CT parameters for PET/CT and SPECT/CT with IMPACT software. Table1 shows the results. The 37% of the pts repeated the 123 I-MIBG SPECT/CT more than three times in two years, while 27, 5% of pts performed two times 18 F-FDG PET/CT. Conclusions: The diagnostic procedures involving radiations expose pts to a risk of stochastic cancer related to age and gender (figure1). The fulfil of diagnostic reference values for all scans is mandatory, furthermore the administered activity and CT parameters personalisation for adult and paediatric pts, particularly in repeated acquisitions, is of primary importance – always preserving the image quality.